Peran BUMDES Dalam Meningkatkan Pertumbuhan Ekonomi Pedesaan Melalui Penguatan Sumber Daya Manusia - Zulifah Chikmawati (Jurnal Istiqro, 2019)
The rural economy is still an obstacle in the lives of villagers. Paradigm built in rural communities is poverty, deterioration, backwardness, and various forms of discrimination against the development and growth in rural communities. The most fundamental aspect is the inability of rural communities to manage, develop, and optimize the potential of local and village resources to improve the welfare of the community. Public welfare a major goal in the various aspects of life of the nation. Various programs have been carried out by the government in order to develop and build the local economy with a variety of perspectives and methods. Improve the economy of rural communities in Act 6 of 2014 About the Village provides an option that is expected to form a government village BUMDes (village-owned enterprises). BUMDes provide the widest possible space for the village government to regulate independent local potential and innovation with various facilities provided by the government ole much as 1.4 Billion funding for rural development effectively and efficiently, including infrastructure, education, economy, and programs for welfare for villagers to develop into a concrete and comprehensive. BUMDes optimization by building trust to the community through active participation in parallel that can be done together. BUMDes accommodate all local potential yield components to be managed and developed into a superior product as the process of economic development of society. Excellent products developed through BUMDes can be marketed nationally and internationally in order to improve the quality of the local potential. Therefore, BUMDes will be central to the economy of rural communities to national development. Nation building should start from the development of the village as the spearhead of government. Back to the village to build a village for the better